2004
DOI: 10.1001/archinte.164.12.1313
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic and Sex Differences in the Prevalence, Treatment, and Control of Dyslipidemia Among Hypertensive Adults in the GENOA Study

Abstract: Dyslipidemia is highly prevalent in hypertensive adults. Fewer than one third of these adults are drug-treated, and fewer than half of those treated achieve recommended goals. Our findings suggest that an alarming 9 of 10 dyslipidemic hypertensive adults have untreated or undertreated dyslipidemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
110
0
4

Year Published

2006
2006
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 168 publications
(122 citation statements)
references
References 31 publications
8
110
0
4
Order By: Relevance
“…This is confirmed by estimates of the prevalence of dyslipidaemia in hypertensive patients in surveys and studies of electronic medical records which range from approximately 20 to 50%. 3,4,[7][8][9][10] In the GPRD, we also found a low prevalence of recording for other cardiovascular risk factors. In UK general practice, screening for the presence of diabetes 33 and proteinuria 34 is not routinely performed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is confirmed by estimates of the prevalence of dyslipidaemia in hypertensive patients in surveys and studies of electronic medical records which range from approximately 20 to 50%. 3,4,[7][8][9][10] In the GPRD, we also found a low prevalence of recording for other cardiovascular risk factors. In UK general practice, screening for the presence of diabetes 33 and proteinuria 34 is not routinely performed.…”
Section: Discussionmentioning
confidence: 99%
“…Hypertension seldom occurs in isolation from other risk factors and is often accompanied by conditions such as glucose intolerance, obesity, left ventricular hypertrophy and dyslipidaemia (including elevated total cholesterol and elevated lowdensity lipoprotein cholesterol). 1 The clustering of multiple cardiovascular risk factors in individuals is common, [1][2][3][4] and it has been observed that the impact of concurrent risk factors on cardiovascular disease (CVD) is more than additive. 5,6 Dyslipidaemia is found in a high proportion of hypertensive patients, 4,[7][8][9][10][11] and the presence of both conditions results in a significant increase in the risk of CVD.…”
Section: Introductionmentioning
confidence: 99%
“…14 Recruitment and subject characteristics in Phase I 15 and Phase II 16 of the GENOA study have been previously described. All the participants for the present study were non-Hispanic white subjects residing in Olmsted County, MN, USA.…”
Section: Study Populationmentioning
confidence: 99%
“…Serum creatinine, glucose, total cholesterol, HDL cholesterol, and triglyceride concentrations and urine albumin, total protein, and creatinine concentrations were measured by standard methods on a Hitachi 911 Chemistry Analyzer (Roche Diagnostics, Indianapolis, IN) (13,14). The eGFR was calculated using the Modification of Diet in Renal Disease (MDRD) equation: eGFR ϭ 186.3 ϫ (serum creatinine)…”
Section: Laboratory Measurementsmentioning
confidence: 99%